Optimization of Small Pb-Bi Cooled Modified CANDLE Burnup based Long Life Fast Reactors - Zaki Su'ud; Nur Asiah Aprianti; Rida Siti NM; Hiroshi Sekimoto (Institut Teknologi Bandung, 2012)
In this study optimization of modified CANDLE burnup scheme based long life Pb-Bi Cooled Fast Reactors with natural Uranium as Fuel Cycle Input for small long life reactors has been performed. In this design the reactor cores are subdivided into several parts with the same volume in the axial directions. The natural uranium is initially put in region 1, after one cycle of 10 years of burn-up it is shifted to region 2 and the region 1 is filled by fresh natural uranium fuel. This concept is basically applied to all regions, i.e. shifted the core of I’th region into I+1 region after the end of 10 years burn-up cycle. In this paper we discuss the characteristics of several designs of small long life Pb-Bi cooled fast reactors with modified CANDLE burn-up scheme. Four power levels of 250MWt, 400MWt, 600MWt, and 800MWt were investigated. For 250MWt and 400MWt cores we employed 67.5% high fuel volume fraction nitride fuels with large pin diameter of 1.35 cm while for 600and 800MWt cores we employed 60% fuel volume fraction nitride fuel with 1.2 cm pin diameter. The results show that all cores show similar trend in k-eff pattern change, k-inf pattern change, conversion ratio pattern change, and U-238 and Pu-239 atomic density pattern changes. Maximum discharged burn-up is in the range of 26-33%HM, while peak power density is in the range of 340-410 W/cc.